Curriculum: A Brief Focus on Construction Management - Hairuddin Mohammad,; Hassan, Padzil Fadzil; Yaman, Siti Khalijah; Zainun, Noor Yasmin (Multidisciplinary Applied Research and Innovation, 2022)
Curriculum is an important part of formal education and training, albeit for general learning programmes. Although it is usually considered during the design phase for any programme, its interconnected nature between curriculum and other elements was arguably being misunderstood. This was apparent especially for greenhorn individuals/organisations that were newly involved in any programme development. Thus, this paper reviews the underlying concept and elements of the curriculum and further focuses on construction management programme development as a point of interest. Past selected manuscripts were taken based on two keywords, i.e. curriculum and construction management. In a nutshell, the development process for any programme need to have clear and concise targeted goals. This was followed by the expected learning outcomes for a particular curriculum. Nevertheless, synergetic supports from essential stakeholders from the beginning of programme development are inevitable to ensure its effectiveness.